A Comprehensive Review of Bhringraj (Eclipta alba L.) from Ayurveda Perspective - Yadav, Nikhil Ravindra; Huddar, Shreedevi (International Research Journal of Ayurveda & Yoga, 2024)
Background: Eclipta alba L. is commonly known as Bhringraj, a plant well known in Ayurveda for its varied medicinal uses. Plant extracts of Bhringraj have been used for a variety of cures, among which the commonly known properties of its extract are anti-hepatotoxic, anti-diabetic, anti-inflammatory, and hair rejuvenator. The present review of Bhringraj aims to explore its literature in Ayurveda texts as well as its current research. Materials and Methods: Exploration of Ayurveda literature was done from Ayurveda classical texts as well as information from internet research databases was collected and presented in an organized manner. Result: Bhringraj has been widely described in various samhitas and nighantus with various clinical indications such as Kasa, Krimi, Swasa, Kushta, Dantya, Keshya, Pandu, and Shiroroga. Conclusion: Bhringraj holds a wide potential as per the references obtained in the present review and more studies should be conducted to tap its potential in clinical trials for human benefit.